Bufo Fergusonii (Ferguson's Toad). Ecology - Das, Indraneil; Martin, Gerard N. (Society for the Study of Amphibians and Reptiles (SSAR), 1998)
Bufo fergusonii Boulenger 1892, is a small (adult females to 46 mm SVL), terrestrial bufonid endemic to peninsular India. It also has been reported from Sri Lanka (Dutta. 1997. Amphibians of India and Sri Lanka [Checklist and Bibliography].